Protein expression : a practical approach - Higgins, S. J. (Steve J.); Hames, B. D. (Practical approach series, 1999)
Protein Expression: A Practical Approach and its companion volume Post-translational Modification: A Practical Approach complete the mini-series of Practical Approach books covering the synthesis and subsequent processing of proteins. Protein Expression: A Practical Approach details the expression of cloned DNA or RNA templates in all the major in vivo and in vitro systems. The in vivo systems covered are cultured mammalian cells, the yeasts Saccharomyces cerevisiae and Pichia pastoris, baculovirus, Xenopus oocytes, and prokaryotic cells. Cell-free systems of both eukarytotes and prokaryotes are described, including the prokaryotic systems that offer copuled transcription- translation. There is also a chapter on monitoring protein expression. The post- translational fate of proteins is covered in Post-Translational Processing: A Practical Approach.